Sistem Sistem Informasi Akreditasi Online Multi-LAM untuk Manajemen Dokumen Program Studi - Eko Wahyu Wibowo; M. Iman Wahyudi; Angga Kurnia Putra (Puslitbang Sinergis Asa Professional, 2026)
Study-program accreditation requires supporting evidence to be organised in a valid, current, and traceable manner. This need becomes more complex when study programs within one faculty are evaluated by different independent accreditation agencies, such as LAMSAMA and LAM INFOKOM. This study develops a web-based multi-accreditation-agency information system for managing accreditation documents at a Faculty of Science and Technology. The system was developed using the System Development Life Cycle, which consists of requirements analysis, design, coding, testing, and maintenance. The results show that the system supports three user roles, document mapping by study program, accreditation agency, and criteria, as well as upload, download, validation, revision, and monitoring functions. Black-box testing indicates that the main functional scenarios run as expected. The proposed system contributes an adaptive document management model that can be updated when accreditation criteria or agency schemes change.